Clerodane diterpenoids from Dodonaea viscosa and their inhibitory effects on ATP citrate lyase. (March 2021) - Lei, Chun; Wang, Xiao-Hang; Liu, Yi-Nan; Zhao, Ting; Hu, Zhu; Li, Jing-Ya; Hou, Ai-Jun
Abstract: Six undescribed clerodane diterpenoids, dodovisins A−F, together with nine known ones, were isolated from the aerial parts of Dodonaea viscosa (L.) Jacq. Their structures were elucidated by extensive spectroscopic techniques, X-ray crystallographic analysis, and ECD calculation. Dodovisins A and B possess a rare carbon skeleton featuring a bicyclo[6.2.0]decane motif. Dodovisins C−E represent the first clerodane diterpenoids with a 4(5 → 19)- abeo -2, 4, 10(1)-triene moiety. Dodovisins A, E, and strictic acid showed potent inhibitory activities against ATP citrate lyase. Graphical abstract: Image 1 Highlights: Fifteen clerodane diterpenoids were isolated and identified from Dodonaea viscosa. Six diterpenoids with structural diversity are undescribed. Some of the diterpenoids showed potent inhibition against ATP citrate lyase.